Iraq Crude Oil Exports – July, August, September/ 2020 - SOMO, Ministry of Oil / Oil Marketing Company (Journal of Petroleum Research and Studies, 2022)
Table 1. Iraq Crude Oil Exports – July 2020 Table 2. Iraq Crude Oil Exports – August 2020 Table 3. Iraq Crude Oil Exports – September 2020